Patent Publication and the Market for Ideas - Hegde, Deepak; Luo, Hong (Management Science, 2018)
In this paper, we study the effect of invention disclosure through patent publication on the market for ideas. We do so by analyzing the effects of the American Inventor’s Protection Act of 1999 (AIPA)—which required U.S. patent applications to be published 18 months after their filing date rather than at patent grant—on the timing of licensing deals in the biomedical industry. We find that post-AIPA U.S. patent applications are significantly more likely to be licensed before patent grant and shortly after 18-month publication. Licensing delays are reduced by about 10 months, on average, after AIPA’s enactment. These findings suggest a hitherto unexplored benefit of the patent system: by requiring inventions to be published through a credible, standardized, and centralized repository, it mitigates information costs for buyers and sellers, and thus facilitates transactions in the market for ideas. The online appendix is available at https://doi.org/10.1287/mnsc.2016.2622 . This paper was accepted by Bruno Cassiman, business strategy.